PENERAPAN GOAL PROGRAMMING UNTUK OPTIMASI JAM KERJA OPERATOR MOLDING PADA PENJADWALAN DI PT. ABC - Luthfianto, Saufik; Saputri, Rita; Anthara, , I Made Aryantha (Inaque : Journal of Industrial and Quality Engineering, 2024)
Arranging work schedules for operators is one of the problems every business faces. The regulations set by the company, the amount of man power available, and the distribution of work weights are determining factors in the scheduling system. This operator scheduling problem can be modeled as an integer programming problem. Integer programming is an optimization technique with a linear objective function, linear constraint function, and decision variables in the form of integers. In this research, we will discuss the use of goal programming to provide a solution to the scheduling problem of molding operators at PT ABC which still uses manual methods in scheduling. The method used is the integer goal programming method which is a method that can provide solutions to multi-objective problems. This research was carried out with the aim of finding out the correct modeling model for molding operator scheduling using the goal programming method by fulfilling all the constraints that have been set and the desired goal, namely minimizing the total molding operator shift with the help of Lingo software for subsequent implementation at PT ABC.